2017
DOI: 10.1063/1.4997588
|View full text |Cite
|
Sign up to set email alerts
|

Negative spin Hall magnetoresistance of Pt on the bulk easy-plane antiferromagnet NiO

Abstract: We report on spin Hall magnetoresistance (SMR) measurements of Pt Hall bars on the antiferromagnetic NiO(111) single crystal. An SMR with a sign opposite of conventional SMR is observed over a wide range of temperatures as well as magnetic fields stronger than 0.25T. The negative sign of the SMR can be explained by the alignment of magnetic moments being almost perpendicular to the external magnetic field within the easy plane (111) of the antiferromagnet. This correlation of magnetic moment alignment and exte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

25
168
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 167 publications
(197 citation statements)
references
References 62 publications
(101 reference statements)
25
168
1
Order By: Relevance
“…It crystallizes in a rock salt structure with a lattice constant of 4.1769 Å [20] at 300 K. It was recently shown that NiO can act as a spin current amplifier in spin Seebeck experiments, and can additionally be a spin current generator when a thermal gradient is applied [21,22,23,24], making NiO a key material for thermoelectric devices. Further, the latest studies report on a temperature-dependent sign change in the spin hall magnetoresistance for nickel oxide on ferromagnetic insulator [25,26]. Thus, there is a possibility to use it as a spin filter.…”
Section: Introductionmentioning
confidence: 99%
“…It crystallizes in a rock salt structure with a lattice constant of 4.1769 Å [20] at 300 K. It was recently shown that NiO can act as a spin current amplifier in spin Seebeck experiments, and can additionally be a spin current generator when a thermal gradient is applied [21,22,23,24], making NiO a key material for thermoelectric devices. Further, the latest studies report on a temperature-dependent sign change in the spin hall magnetoresistance for nickel oxide on ferromagnetic insulator [25,26]. Thus, there is a possibility to use it as a spin filter.…”
Section: Introductionmentioning
confidence: 99%
“…The current is applied along the x direction (φ = 0°). 20 The red squares and blue triangles are experimental values. The green solid line is the simulated magnetoelastic anisotropy energy.…”
mentioning
confidence: 99%
“…However, the effective manipulation of the antiferromagnetic moment is challenging due to the insensitivity of AFMs to external magnetic fields, which is also the crucial issue in AFM‐based spintronics. Many efforts have been made to solve this problem via magnetic control by a strong magnetic field or field cooling,2,10,11 electrical control by a current or an electric field,3,12–16 and optical control based on a thermal or an electronic excitation 17–19…”
Section: Introductionmentioning
confidence: 99%